Singapore : riding the wave of globalization. - Pong, Ling Cherng. (2008)
This paper discusses the economicdimensions of globalization and, drawing on the conceptual framework proposed by Johnston, Darbar and Echeverria (1997), chronicles the sequencing of the capital accountliberalization of Singapore. The information reviewed is for the period 1961-2001.